2022
DOI: 10.1126/scitranslmed.abm9043
|View full text |Cite
|
Sign up to set email alerts
|

NK cells with tissue-resident traits shape response to immunotherapy by inducing adaptive antitumor immunity

Abstract: T cell–directed cancer immunotherapy often fails to generate lasting tumor control. Harnessing additional effectors of the immune response against tumors may strengthen the clinical benefit of immunotherapies. Here, we demonstrate that therapeutic targeting of the interferon-γ (IFN-γ)–interleukin-12 (IL-12) pathway relies on the ability of a population of natural killer (NK) cells with tissue-resident traits to orchestrate an antitumor microenvironment. In particular, we used an engineered adenoviral platform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 74 publications
2
40
0
2
Order By: Relevance
“…Of note, we found that NK cell depletion abolished the increased recruitment of cDC1s into the tumor-bearing lungs in BCG-treated mice (Fig 5e). In concordance with this result, we found that IV BCG enhanced the capacity of NK cells to produce the chemokine CCL5, which has been described crucial to mediate cDC1 recruitment 33,35 Our data revealed that a higher percentage of lung NK cells in BCG-treated mice secreted CCL5 compared to controls (Figure 5f), providing an explanation for the observed NK-cell mediated recruitment of cDC1s to the tumor-bearing lung. In line with these results, IV BCG increased CCL5 protein levels in whole-lung lysates, in an NK cell-dependent fashion (Fig 5g), confirming that in our model NK cells are the main source of CCL5 in response to IV BCG treatment.…”
Section: Activation Of Nk Cells By IV Bcgsupporting
confidence: 88%
“…Of note, we found that NK cell depletion abolished the increased recruitment of cDC1s into the tumor-bearing lungs in BCG-treated mice (Fig 5e). In concordance with this result, we found that IV BCG enhanced the capacity of NK cells to produce the chemokine CCL5, which has been described crucial to mediate cDC1 recruitment 33,35 Our data revealed that a higher percentage of lung NK cells in BCG-treated mice secreted CCL5 compared to controls (Figure 5f), providing an explanation for the observed NK-cell mediated recruitment of cDC1s to the tumor-bearing lung. In line with these results, IV BCG increased CCL5 protein levels in whole-lung lysates, in an NK cell-dependent fashion (Fig 5g), confirming that in our model NK cells are the main source of CCL5 in response to IV BCG treatment.…”
Section: Activation Of Nk Cells By IV Bcgsupporting
confidence: 88%
“…Therefore, the possibility of recruiting cDC1 into tumors, as well as improving their functionality, could prove to be useful strategies for increasing antitumor immunity and response to immunotherapies. Remarkably, an additional role of NK cells in the immune response to cancer has been demonstrated by recent publications that showed NK cells controlling the levels of intratumoral cross-presenting cDC1s, by expression of FLT3 Ligand [ 92 ] and chemokines, such as CCL5 (RANTES) and XCL-1/XCL-2 [ 91 , 93 ]. In patients with melanoma, levels of NK cells and intratumoral cDC1s even positively correlated with increased survival and predicted response to anti-PD-1 therapy [ 92 ].…”
Section: Role Of Nk Cells In Creating a More Inflamed Environment (To...mentioning
confidence: 99%
“…In particular, we found that the proliferating NK cell subset is enriched for a tissueresidency signature, a finding which is in accordance with previous data from our group, in which we show an association between the presence of tissue-resident NK cells and response to immunotherapies in patients. 67 Finally, with our flow cytometric analysis, we identified one distinctive effect in LAG-3 surface upregulation in different CD4 + and CD8 + T cell subsets as a biomarker of response to anti-LAG-3 treatment, which does not require anti-PD-1. Similarly, in a mouse model, a bsAb targeting LAG-3 and PD-L1 was shown to enhance T cell activation and increase soluble LAG-3 in plasma.…”
Section: Discussionmentioning
confidence: 76%
“…In particular, we found that the proliferating NK cell subset is enriched for a tissue-residency signature, a finding which is in accordance with previous data from our group, in which we show an association between the presence of tissue-resident NK cells and response to immunotherapies in patients. 67 …”
Section: Discussionmentioning
confidence: 99%